Dialogiczna otwartość teologii kardynała Waltera Kaspera w nurcie dziedzictwa katolickiej szkoły tybingeńskiej - Podhorecki, Norbert (Poznańskie Studia Teologiczne, 2016)
Our masters, next to which we grew up, and certain environments that have formed – on many levels – not only our consciousness, but even the methodology of our thinking and activities, play a very significant role in the shaping the way we look at and understand the world, and the ideas, which we adhere to. Cardinal Walter Kasper repeatedly relied in his works on his spiritual relationship with the principles of Catholic school in Tübingen of the nineteenth century, considering it as an outstanding model for attachment to ecclesiastical tradition and at the same time for the openness to the dialogue with the contemporary world. This text presents one of the theological principles of the school in Tübingen – dialogical openness of the theology to the contemporary issues – in the work and thought of Cardinal Walter Kasper.